Breast hamartoma: reassessment of an under‐recognised breast lesion. Issue 2 (22nd September 2021) - Alran, Léonie; Chamming's, Foucauld; Auriol‐Leizagoyen, Sophie; Velasco, Valérie; Deleau, Florian; Brouste, Véronique; Bonhomme, Benjamin; Ben Rejeb, Houda; Marty, Marion; MacGrogan, Gaëtan
Abstract : Aims: Breast hamartomas are an under‐recognised lesion because they lack a distinctive microscopic appearance. Microscopic diagnosis can often conclude 'no significant lesion' or 'normal breast tissue', leading to repeated biopsies and diagnostic delay. We describe the histological, immunohistochemical and radiological features of breast hamartomas with the aim of identifying specific signs to facilitate their diagnosis and to differentiate them from normal breast and fibroepithelial lesions. Methods and results: Forty‐seven breast hamartomas were reassessed (histological diagnosis and imaging features). An immunohistochemical study [oestrogen receptor (ER), progesterone receptor (PR), CD34, high‐mobility group A2 (HMGA2)] was performed. On breast imaging, hamartomas most often presented as probably benign solid masses with circumscribed margins and variable densities. Histologically, breast hamartomas resembled normal breast, although their stromal component was predominant, separating randomly scattered epithelial elements with areas of pure collagenous stroma. Pseudoangiomatous stromal hyperplasia (PASH) was present in 93.6% of cases and CD34 antibody highlighted intralobular, perilobular and interlobular distribution of CD34‐positive fibroblasts. By comparison, CD34 was mainly expressed in the intralobular normal breast tissue stroma. Hamartoma stromal cells expressed HMGA2, ER and PR in 79%, 66% and 76.3% of our cases, respectively, compared to 7.7%, 23% and 19% in normal breast tissue, respectively ( P  < 0.0001; P  = 0.0005; P  < 0.0001). Conclusions: After ascertaining that core needle biopsy is effectively intralesional, breast hamartomas can be diagnosed with confidence by taking into account the presence of stromal changes, PASH, interlobular distribution of CD34‐positive fibroblasts, HMGA2 and hormonal receptor stromal expression. Abstract :